PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT FACILITATOR AND EXPLAINING DALAM PEMBELAJARAN BILINGUAL TERHADAP HASIL BELAJAR TEMATIK SISWA KELAS V - Noge, Maria Desidaria; Oli, Yohanes Mite; Wau, Maria Patrisia (JURNAL PENDIDIKAN DASAR NUSANTARA, 2022)
This research aimed at finding out the effect of cooperative learning models of Student Facilitator and Explaining in Bilingual learning of the thematic learning achievement of class V in the group VI district of Boawae District Nagekeo. This research was experimental research using the research design of pseudo experiments, with the research draft "Posttest Only Control Group Design". The subject in this study was students class V of Padhapae Primary School as an experimental group totaled 28 students, and Raja Primary School students as a control group totaled 25 students. Test result data were analyzed by statistics descriptive quantitative. From the results of the analysis obtained t-test value 4.038 is greater than 2.021, with its significance value was 0.000 smaller than 0.05, then the decision was H0 refused and H1 accepted. Based on the posttest results in the experimental group gained an average of 72.35 while the control group gained an average of 60.64. The hypothesis test results showed that there was a significant influence in the implementation of a cooperative learning model for Student Facilitator And Explaining in Bilingual learning of the thematic learning achievement of the V-class students in Boawae subdistrict. Nagekeo Regency.